Perchance to Dream - Mantchev, Lisa (New York : Feiwel and Friends, 2010)
Bertie, who is blessed with word magic, and her fairy sidekicks seek to save Nate, who has been kidnapped by the Sea Witch, but Bertie is torn between Nate and Ariel, an air spirit who loves Bertie enough to die for her.
Sequel to: Eyes like stars.
Keywords: Theater -- Fiction; Magic -- Fiction; Fairies -- Fiction; Orphans -- Fiction; Interpersonal relations -- Fiction